The Effects of a Workplace Health Promotion Program to Decrease Cadmium Exposure Levels in Nickel-Cadmium Battery Workers - Sovičová, Miroslava; Tomášková, Hana; Carbolová, Lenka; Šplíchalová, Anna; Baška, Tibor; Hudečková, Henrieta (Acta medica academica, 2019)
OBJECTIVE: Cadmium exposure is a common problem in the production of nickel-cadmium batteries. However, keeping the respective legislative occupational and safety policies is essential, but there are problems with compliance. We analysed the effect of strategies to increase compliance with precautions during 20132015 on 59 workers at a nickel-cadmium battery factory. MATERIAL AND METHODS: A health promotion program was implemented in two phases. The first phase included comprehensive education on the importance of appropriate behaviour and changes to the sanitation program. The second phase included renovation of sanitary facilities and modernization of the air exhaust ventilation. RESULTS: The initial median cadmium urinary level in workers was 1.9 µg/g creatinine. After the first phase of interventions, levels dropped to 1.0 µg/g creatinine. After the second phase no significant further decrease was observed. CONCLUSION: Comprehensive education and changes in the sanitation program were able to halve cadmium levels and can be considered a useful and cost-effective preventive tool.
Keywords: Cadmium; Manufacturing and Industrial Facilities; Humans; lidé; výrobní a průmyslová zařízení; zdroje elektrické energie; pracoviště; otrava kadmiem; Workplace; Electric Power Supplies; pracovní expozice; Occupational Exposure; Female; Male; Adult; Occupational Health; mužské pohlaví; podpora zdraví; hygiena práce; Cadmium Poisoning; ženské pohlaví; nikl; dospělí; Nickel; kadmium; Health Promotion